Effectiveness of Bali Government's Policy in Continuous Giving of Grants to The Bali Sports Committee - Dirgantari, Made Yandi (Fakultas Syariah INSURI Ponorogo, 2023)
The provision of continuous grants to the Indonesian National Sports Committee (KONI) Bali amounted 39 billion rupiahs a year, considered ineffective, considering that there are still cases of theft of these grants. Examining more deeply the level of effectiveness of grant funding is an important thing to do, especially in the Province of Bali which is one of the areas that is often used as the organizer of sporting events. This research is an empirical research that is descriptive in nature with an empirical legal approach. This research took place in KONI Bali and Office of Education, Youth and Sports (Disdikpora). The data used in this study consisted of primary and secondary data obtained through documentation, observation and interviews. Data then being analyzed using qualitative descriptive method Results indicate that provision of grants to KONI Bali has met the principle of effectiveness, in accordance with Disdikpora Bali which states that value of the grants given shows a significant increase in athlete achievement at the national and international tournament. Obstacles found in terms of communication, resources and bureaucracy. The provision of grants made by the regional government to KONI Bali complies with the provisions of Law 11 of 2022, Permendagri 77 of 2020 and Pergub Bali No 3 of 2019.